An anomalous foveal OCT-sign after posterior capsule rupture in cataract surgery: Complicated cataract surgery maculopathy. Issue 6 (November 2021) - Talli, Pietro Maria; Pedrotti, Emilio; Sacconi, Riccardo; Monterosso, Cristina; Caretti, Luigi
Purpose: To report a series of novel optical coherence tomography (SD-OCT) foveal abnormalities, that we called "T-sign, " that were noticed after a complicated cataract surgery with posterior capsule rupture and vitreous loss. Methods: Retrospective case series of persistent foveal changes that incurred after anteroposterior vitreo-foveal traction secondary to phacoemulsification in presence of posterior capsule rupture. Results: The study included three eyes of three patients that incurred in complicated cataract surgery and intraoperative vitreo-foveal traction. During 8-month follow-up period peculiar abnormalities in fundus examination and in OCT scans were reported in all cases. Conclusion: Phacoemulsification in presence of posterior capsule rupture could induce a vitreo-foveal strain that could be transmitted to the cone outer segment tips (COST line) and inner–outer segment (IS/OS) junction. This focal stress is liable for "T-sign, " a persistent SD-OCT abnormality that induce a visual impairment and a slight metamorphopsia in the fixation point. Summary statement: All over the world, more than 9.5 million cataract surgeries are completed each year. 1 During surgery, many intraoperative complications could occur, and capsule rupture with vitreous loss is a frequent event. Phacoemulsification in presence of a wide posterior capsule rupture and vitreo-macular adhesion could induce a typical modification of the foveal structure and a permanent visual impairment.